2022
DOI: 10.1111/ecca.12421
|View full text |Cite
|
Sign up to set email alerts
|

Turning a ‘Blind Eye’? Compliance with Minimum Wage Standards and Employment

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…On the one hand, enforcement's mechanical impact would be to increase their wages. On the other hand, prior research has discussed and provided evidence for the hypothesis that evasion may be a strategy through which firms seek to absorb the cost shock from minimum wage increases while laying off as few workers as possible (Garnero and Lucifora, 2022;Badaoui and Walsh, 2022;Clemens, 2021). 13 This highlights a potential trade-off between enforcement, on the one hand, and firm responses that might more 13 A conceptually related line of work has found that the minimum wage interacts with tax compliance and that taxevading firms may, by increasing their reporting rates, room to comply with minimum wages without actually increasing net pay (Tonin, 2011;2013;Gavoille, and Zasova, 2021).…”
Section: Section Vi: Discussion and Conclusionmentioning
confidence: 99%
“…On the one hand, enforcement's mechanical impact would be to increase their wages. On the other hand, prior research has discussed and provided evidence for the hypothesis that evasion may be a strategy through which firms seek to absorb the cost shock from minimum wage increases while laying off as few workers as possible (Garnero and Lucifora, 2022;Badaoui and Walsh, 2022;Clemens, 2021). 13 This highlights a potential trade-off between enforcement, on the one hand, and firm responses that might more 13 A conceptually related line of work has found that the minimum wage interacts with tax compliance and that taxevading firms may, by increasing their reporting rates, room to comply with minimum wages without actually increasing net pay (Tonin, 2011;2013;Gavoille, and Zasova, 2021).…”
Section: Section Vi: Discussion and Conclusionmentioning
confidence: 99%
“…10 If the fine were linear in the amount of underpayments, the firm would either comply with the law or just pay the competitive wage (see, for example, Ashenfelter and Smith (1979), Grenier (1982), or Chang and Ehrlich (1985)). Alternatively, an interior solution can result, for example, if the firm is strictly risk-averse (Yaniv 2001) or faces a detection probability or expected fine that are increasing and strictly convex in the number of underpaid minimumwage workers (Bhorat et al 2015, Garneiro andLucifora 2022).…”
Section: Optimal Choicesmentioning
confidence: 99%
“…Our contribution is related to (1) theoretical analyses of minimum wage underpayments, (2) empirical investigations of such behaviour, and (3) studies analysing the effects of works councils. Many theoretical analyses consider minimum wage underpayments in competitive settings (see, for example, Ashenfelter and Smith (1979), Chang and Ehrlich (1985), Chang (1992), Yaniv (2001), Bhorat et al (2015), or Garneiro and Lucifora (2022)). Yaniv (1988) marks an initial exploration of underpayments in a monopsonistic framework, assuming that labour supply is increasing in the wage.…”
Section: Introductionmentioning
confidence: 99%
“…In more general terms, the context shapes the way firms react to wage floors and the margins along which they adjust to the policy change. In this regard, Clemens (2021) highlights that labour demand is just one of the possible adjustment mechanisms, and firms can (and will) adapt also by changing prices (Harasztosi and Lindner, 2019), compressing profits (Draca et al, 2011), increasing productivity (Dube, 2019) or even by means of non-compliance (Garnero and Lucifora, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…First, although some proposals on the matter have been put forward in recent years, it is one of the few European countries where no statutory minimum wage exists, and wage floors are provided by collective agreements that only apply to signatory firms. Second, Garnero and Lucifora (2021) document a significant phenomenon of non-compliance, which is facilitated by the large number of often (partly) overlapping agreements. Third, the Italian economy exhibits some worrying macro-trends, such as slow output growth, low business turnover, and increasing income inequality, which have been regarded as symptoms of widespread market power (De Loecker et al, 2020), such as slow output growth, low business turnover, and increasing inequality.…”
Section: Introductionmentioning
confidence: 99%